Formulation Development and Optimization of Press Coated Tablets of Ranitidine HCl by using 32 Factorial Design - Boddu, Prasanthi; Mudili, Nagabhushan; ponukumati, Uma (Jordan Journal of Pharmaceutical Sciences, 2021)
The main aim of the present work is to formulate and evaluate a chronotherapeutic drug delivery system of ranitidine hydrochloride using suitable mucoadhesive polymers by press coating technique. For elucidating the effect of formulation factors of press coated tablets a 32 full factorial design was employed. The effect of two factors, ratio of hydroxy propyl methyl cellulose (HPMC) K4M and ethyl cellulose (EC) in the core (X1) and ratio of HPMC K4M and carbopol 934P in the coat(X2) as independent variables. Y1 (drug release lag time), Y2 (% drug release after 6 hours) and Y3 (mucoadhesion strength) were selected as dependent variables. Thirteen formulations were formulated and subjected to various physiochemical evaluations like weight variation, friability, hardness, drug content, in vitro drug release and kinetic studies, swelling index and ex vivo mucoadhesion studies. The optimum formulation consists of ranitidine HCl 150mg, HPMC K4M: EC (0.72:1) in the inner core and HPMC K4M: carbopol 934P (1:1) in the outer coat with drug release lag time 1.89 hrs, cumulative % drug release after 6 hrs 41.15% and mucoadhesion strength 43.67 g. Ranitidine HCl tablets exhibited zero order release kinetics, resulting in regulated and complete release until 11 hrs.